Distribution patterns, inter-and intra-host dynamics of an emerging salmonid parasite T. bryosalmonae across temporal and spatial scales - Lauringson, Magnus (Estonian University of Life Sciences, 2024)
A Thesis for applying for the degree of Doctor of Philosophy in Agricultural Sciences. Väitekiri filosoofiadoktori kraadi taotlemiseks põllumajandusteaduste erialal. ABSTRACT. Global climate change is shifting the physical and chemical properties of freshwater ecosystems, involving increased water temperature, altered hydrological regime and nutrient concentrations. These changes influence particularly cold-water macro vertebrates, such as salmonids, resulting in loss of habitat and population declines. The physiochemical alternations caused by climate change also have an effect on the biotic environment, including changes in virulence, pathogenicity, distribution and prevalence of pathogens and diseases. One emerging widespread illness is salmonid specific proliferative kidney disease (PKD), caused by myxozoan parasite Tetracapsuloides bryosalmonae, which is primarily affecting juvenile fish during their first growth summer. PKD causes hyperplasia in kidney and spleen tissue, anemia and external clinical signs include abdominal swelling and pale gills. Myxozoans are endoparasites, who have evolved from free-living cnidarians and typically possess a complex two-host life-cycle, involving an invertebrate and vertebrate host. For myxozoan T. bryosalmonae, cycling occurs between freshwater bryozoans and salmonid hosts. In Europe, native brown trout (Salmo trutta), Atlantic salmon (Salmo salar), European grayling (Thymallus thymallus), Arctic charr (Salvelinus alpinus) and European whitefish (Coregonus lavaretus), as well as non-native rainbow trout (Oncorhynchus mykiss) are susceptible to T. bryosalmonae (for review see Ros et al., 2022). While the severity of PKD is strongly dependent on water temperature, with disease symptoms progressing with rising temperature, only a few studies have found T. bryosalmonae in northern regions. Moreover, detailed knowledge on the parasite distribution and prevalence is not available in northernmost regions of Europe. Earlier PKD related research has also primarily been ...